157k views
3 votes
Verify the identity 6cos^2(x) -3 = 3 - 6sin^2(x)

User ZephDavies
by
6.1k points

1 Answer

4 votes

Answer:

It is proved that
6\cos ^(2)x -3 = 3 - 6\sin ^(2) x .

Explanation:

We already have the identity of x as
\sin ^(2)x + \cos ^(2)x = 1 .......... (1) .

So, from equation (1) we can write that


\cos ^(2) x = 1 - \sin ^(2) x


6\cos ^(2) x = 6 - 6 \sin ^(2) x


6\cos ^(2) x -3 = 6 - 6 \sin ^(2)x -3


6\cos ^(2)x -3 = 3 - 6\sin ^(2) x

Hence, it is proved that
6\cos ^(2)x -3 = 3 - 6\sin ^(2) x . (Answer)

User DaoWen
by
5.6k points